Business Improvement Strategy for Local ERP Companies in Indonesia: SWOT Method, Fuzzy AHP-TOPSIS - Tampubolon, Rhoni Ilham (Jurnal Penelitian Medan Agama, 2024)
Enterprise Resource Planning (ERP) is a crucial digital system for businesses to increase efficiency and productivity in the digital era. However, a case study company in Indonesia has experienced a decline in sales over the last three years. To improve the company's business, a systematic approach using the SWOT method, fuzzy AHP (F-AHP), and TOPSIS was employed. The SWOT method classifies internal and external factors into strengths, weaknesses, opportunities, and threats, which are then used to formulate alternative strategies using the TOWS matrix. The TOPSIS method prioritizes these strategies based on the SWOT factor weights. Based on the Action Priority Matrix, several strategic priorities were selected to increase the income of the local ERP-producing company in Indonesia: expanding the marketing network, offering a new business scheme, and forming a community to increase brand awareness.